Mutation of FMDV Lpro H138 residue drives viral attenuation in cell culture and in vivo in swine - Azzinaro, Paul A.; Medina, Gisselle N.; Rai, Devendra; Ramirez-Medina, Elizabeth; Spinard, Edward; Rodriguez-Calzada, Monica; Zhu, James; Rieder, Elizabeth; de los Santos, Teresa; Díaz-San Segundo, Fayna (Frontiers in Veterinary Science, 2022)
The foot-and-mouth disease virus (FMDV) leader proteinase (Lpro) is a papain like protease that cleaves the viral polyprotein and several host factors affecting host cell translation and induction of innate immunity. Introduction of Lpro mutations ablating catalytic activity is not tolerated by the virus, however, complete coding sequence deletion or introduction of targeted amino acid substitutions can render viable progeny. In proof-of-concept studies, we have previously identified and characterized FMDV Lpro mutants that are attenuated in cell culture and in animals, while retaining their capacity for inducing a strong adaptive immunity. By using molecular modeling, we have now identified a His residue (H138), that resides outside the substrate binding and catalytic domain, and is highly conserved across serotypes. Mutation of H138 renders possible FMDV variants of reduced virulence in vitro and in vivo. Kinetics studies showed that FMDV A12-LH138L mutant replicates similarly to FMDV A12-wild type (WT) virus in cells that do not offer immune selective pressure, but attenuation is observed upon infection of primary or low passage porcine epithelial cells. Western blot analysis on protein extracts from these cells, revealed that while processing of translation initiation factor eIF-4G was slightly delayed, no degradation of innate sensors or effector molecules such as NF-κB or G3BP2 was observed, and higher levels of interferon (IFN) and IFN-stimulated genes (ISGs) were induced after infection with A12-LH138L as compared to WT FMDV. Consistent with the results in porcine cells, inoculation of swine with this mutant resulted in a mild, or in some cases, no clinical disease but induction of a strong serological adaptive immune response. These results further support previous evidence that Lpro is a reliable target to derive numerous viable FMDV strains that alone or in combination could be exploited for the development of novel FMD vaccine platforms.